IMPROVING STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT BY USING PICTURE SERIES AT THE EIGHTH GRADE STUDENTS OF SMP NEGERI 03 SINDANG KELINGI - Tuti Andayani (Linguists : Journal of Linguistics and Language Teaching, 2015)
In this collaborative Classroom Action Research (CAR), the researcher tries to analyze andovercome the problem of writing narrative text facing by the eightgrade students of JuniorHigh School. Many students have problem in writing narrative text, especially in getting theidea and composing the idea itself. The formulation problem of this research was‘Can PictureSeries improve the students’ ability in writing narrative text?’ In order to prove it, theresearcher did the classroom action research which is divided into two cycles. Every cycle wasdivided into four stages, including (1) planning, (2) implementing, (3) observing, and (4)reflecting. The research is focus to students’ ability in writing narrative text by getting ideafrom a series of pictures and developing the idea with the guidance from the pictures. Thesamples involved in this research were 20 students from class VIIIC of SMP Negeri 03SindangKelingi, Curup, RejangLebong, academic year 2014/2015. The data were got from thestudents’ achievement in the cycle I and cycle II. The data was analyzed by using quantitativeanalysis data technique. From the analysis, the writer founded that in the cycle I, students gainthe average score 61,35 and in the cycle II the average score was 73,56. There was an increaseof students’ ability in writing narrative text by using picture series